PEMANFAATAN UNIFIED MODELLING LANGUAGE DALAM PERANCANGAN APLIKASI PENCATATAN TRANSAKSI UNIPRO STORE - Peter; Bagus Mulyawan (Fakultas Teknologi Informasi Universitas Tarumanagara, 2025)
Unipro store is a store engaged in the sale of cellphone accessories. Unipro Store conducts product purchase transactions from suppliers. Then, it sells its products back to consumers through various sales media. In addition to providing direct purchase options at the store, Unipro Store also accepts orders via Whatsapp and markets its products through Tokopedia and Shopee. All transactions are still recorded manually using a notebook. Manual recording of transactions makes it difficult for shop owners to search for historical transaction data and has the risk of losing data because there is no backup if the book is lost or damaged. In an effort to overcome these problems, a system design using Unified Modeling Language (UML) was implemented as part of the waterfall methodology to conceptualize an web-based application for transaction recording and stock management. This design aims to streamline the management of purchasing, sales, and product stock data. UML diagrams were employed to model the processes and system structure, providing a clear and organized visualization of the system requirements. The system design approach using UML effectively supported communication among stakeholders, ensuring that the design aligns with requirements and serves as a solid foundation for future development.